BUILDING NETWORK SERVER BASED COMPUTER NETWORK USING WI-FI (WIRELESS FIDELITY) OPERATING SYSTEM IN WINDOWS SERVER 2003 - Muhammad Sugih Prakarsa; Fivtatianti Hendajani, SKom, MM (Jurnal Sistem Komputer, 2006)
Wireless Networking or Wireless LAN is the networking technology that is not using the cable that can be found inside a computer network at the moment.  These technologies use radio waves to make the interaction or communication between the computer unit. Wireless LAN is basically a radio device capable of connecting data communications between computers or a computer to a Local Area Network (LAN) or vice versa. The purpose of this paper is to use the wireless network can be built a LAN network without using cables that give the computer accessing the network. Access Point used as regulator of transmission between computers in a Wireless network. Access Point acts  like a HUB in a network that uses cables.